Answering relevant research questions via careful observation of clinical practice: a fresh look at the old way forward. (25th August 2014) - Matino, D.; Iorio, A.
Abstract: Although many aspects of inhibitor development have been elucidated, the role of switching FVIII product concentrate in the risk of inhibitors development in previously treated patients is still under discussion. To provide their contribution, Aznar et al [9] transparently showed the numerous different brands used over time and the number of patients treated with one or another class of concentrates in their center. This way of inclusively reporting data as generated in routine clinical practice would need to be adopted more broadly among hemophilia treater and scientists. Strength and limitations of the approach are discussed.